Residential demand response scheme based on adaptive consumption level pricing - Haider H.T.; See O.H.; Elmenreich W. (Elsevier Ltd, 2023)
Demand side management; Economics; Electric utilities; Energy utilization; Housing; Sales; Advance metering infrastructure; Aggregate consumption; Consumption levels; Demand response; Energy bills; Pricing scheme; Smart grid; Time of use; Costs; adaptive management; demand-side management; energy conservation; energy use; infrastructural development; price determination; residential energy